O banco mundial e a educação básica no Ceará: modelo de gestão por resultados como estratégia da redução da pobreza de aprendizagem - Alves, Juliana dos Santos (2025)
We seek to identify actions and processes coordinated between the World Bank and the state of Ceará, which have become fundamental to the construction of the state's education as a reference for efficiency in reducing learning poverty over the last few years. Investigating the path to implementing this partnership, we will analyze WB reports on Ceará's educational development, especially regarding the implementation of management for results (MPR). The partnership between the state of Ceará and the World Bank is not new and its scope goes beyond the education sector. However, it became more effective in the 2000s, in the wake of neoliberal ideology and educational reformism that took shape since the 1990s, both at the national and local levels. Articulated with the guidelines of multilateral organizations and focusing on basic learning needs, the state of Ceará implemented changes in the educational system, achieving learning goals that, according to the WB's approach in its reports, transformed Ceará into a model for reducing learning poverty to be followed by other units of the Brazilian federation. As a research methodology, we used bibliographic and documentary research. The analytical perspective is based on historical and dialectical materialism, rooted in the writings of Karl Marx and ontologically recovered by Gyorgy Lukács. As a main, but not only, result, we point out that the articulation between the State of Ceará and the World Bank has made a management and education model prosper, which is seductive due to the idea of reducing learning poverty when, ultimately, it becomes more aligned with the needs of the current phase of capitalism, aggravated by the structural crisis that, according to István Mészàros, has plagued the system since the 1970s.